2019
DOI: 10.18393/ejss.582231
|View full text |Cite
|
Sign up to set email alerts
|

Effects of iron sources and doses on plant growth criteria in soybean seedlings

Abstract: In this study, effects of different iron sources and doses on plant growth criteria in soybean (Glycine max L.) seedlings were investigated. The experiment was conducted according to factorial experimental design with three replications under controlled conditions. Atakişi variety of soybean (Glycine max L.) cultivar was used as a plant material. Three soybean seeds were sown each plastic pot having 1.3 kg soil:sand mixed in 1:1 ratio. Three different Fe sources (FeSO4.7H2O, Fe-EDDHA and nanoFe) were applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…In another study, the lower component yield and weak growth of soybean crop were mainly because of soybean lodging due to the shade of maize in maize-soybean intercropping (Hussain et al, 2021). However, soybean retains its growth and yield under different environmental stresses when fertilized with optimal fertilizer application of N, P, Fe, and Mo (Gai et al, 2017;Gülser et al, 2019;Seleiman et al, 2021;Mirriam et al, 2022;Oliveira et al, 2022). The leaf area is the key source of carbon assimilation and light interception while chlorophyll is an important pigment involved in not only the absorbance of solar energy but also in its transmission and conversion into electrochemical energy.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the lower component yield and weak growth of soybean crop were mainly because of soybean lodging due to the shade of maize in maize-soybean intercropping (Hussain et al, 2021). However, soybean retains its growth and yield under different environmental stresses when fertilized with optimal fertilizer application of N, P, Fe, and Mo (Gai et al, 2017;Gülser et al, 2019;Seleiman et al, 2021;Mirriam et al, 2022;Oliveira et al, 2022). The leaf area is the key source of carbon assimilation and light interception while chlorophyll is an important pigment involved in not only the absorbance of solar energy but also in its transmission and conversion into electrochemical energy.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in Fe concentration was able to reduce the growth of the three seedlings. The results of several studies also reported that increasing the concentration of Fe can reduce plant growth, such as pineapple [18], Vaccinicum macrocarpon [19], soybean [20,21], and Disccorea spp. [22].…”
Section: Discussionmentioning
confidence: 99%
“…Gülser et al (2019) reported that increasing Fe dose from different sources decreases most of the growth‐related attributes except root length of soybean ( Glycine max L.). Similarly, high dose of Fe in rice ( Oryza sativa L.) plant reduces the plant height, number of tillers, and increases panicle sterility (Audebert, 2006b).…”
Section: Fe Toxicity and Its Effect On Various Plant Attributesmentioning
confidence: 99%